KAJIAN KEUNTUNGAN DAN KELAYAKAN USAHATANI JAGUNG MANIS (Zea mays saccharata sturt) DI KELURAHAN LOKTABAT UTARA KECAMATAN BANJARBARU UTARA KOTA BANJARBARU - Zulipah Mahdalena; Yayuk Minta Wahyuningsih (Fakultas Pertanian UVAYA Banjarmasin, 2022)
This study aims to determine the costs, production,revenue, profits and feasibility of sweet corn in Loktabat Utara village, Banjarbaru utara district. The method used in the reasearch is survey and observation method. . The sampling technique used purposive sampling method, so that 10 respondents were obtained. The results of this study indicate that the total production of sweet corns in the loktabat utara village was 18.450 kg/farm, with an average production of 1.845 kg/farm. The everage revinue is IDR.1.236.856/ farm. And the average profit earned during one production prosess is IDR.5.522.738,89/farm. The R/C ratio value obtained is 2,90, it’s can be said that sweet corn farming in Loktabat Utara is feas